SIMULASI FILTER KALMAN UNTUK ESTIMASI SUDUT DENGAN MENGGUNAKAN SENSOR GYROSCOPE - Wahyudi Wahyudi; Adhi Susanto; Sasongko Pramono H; Wahyu Widada (TEKNIK, 2009)
The Kalman filter is a recursive solution to the process linear filtering problem that can remove the noisefrom signal and then the information can useful. The process that use Kalman filter must be approximatedas two equations of linear system, state equation and output equation. Computation of Kalman filter isminimizes the mean of the square error. This paper explore the basic consepts of the Kalman filteralgorithm and simulate its to filter data of gyroscope to get a rotation. The measurement noise covariancedetermines how much information from the sample is used. If measurement noise covariance is high showthat the measurement isn’t very accurate. The process noise covariance contributes to the overalluncertainty of the estimate as it is added to the error covariance matrix in each time step. If the errorcovariance matrix is small the Kalman filter incorporates a lot less of the measurement into estimate ofrotation.